2017
DOI: 10.1002/lsm.22695
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on the transient vascular thermal response to multi‐pulse Nd:YAG laser

Abstract: For multi-pulse treatment, laser parameters are recommended as repetition rate of 10 Hz and pulse number of 10. The incident energy in each pulse should be strong enough to induce blood coagulation through seven or eight pulses and should be lower than the threshold of blood cavitation. Lasers Surg. Med. 49:852-865, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, cavitation was observed immediately after laser irradiation when the concentration of PEG‐GNPs in blood was 2.5 mg/ml. Li et al reported that the formation of cavitation within blood vessels may cause hemorrhage, which should be avoided in clinic. Herein, the injection dosage of PEG‐GNPs should be less enough to prevent the side effect (i.e., formation of cavitation) in blood vessels after laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…However, cavitation was observed immediately after laser irradiation when the concentration of PEG‐GNPs in blood was 2.5 mg/ml. Li et al reported that the formation of cavitation within blood vessels may cause hemorrhage, which should be avoided in clinic. Herein, the injection dosage of PEG‐GNPs should be less enough to prevent the side effect (i.e., formation of cavitation) in blood vessels after laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiment found that vessel constriction was due to the constriction of thrombus induced by laser irradiation. The theoretical investigation revealed that the mechanism for the effective reduction of energy density by multi-pulse Nd: YAG laser was due to enhanced light absorption of the blood with thrombus formation [ 9 ][ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…As computational models are a powerful, fast, and cheap tool to attain useful information on the electrical‐thermal processes associated with energy‐based therapies , this method was used to simulate the electric, thermal and tissue damage response of a two‐dimensional model of cardiac tissue subjected to RF ablation.…”
Section: Methodsmentioning
confidence: 99%